On the limits to solar thermal power: A reply to Trainer - Lilliestam, Johan; Pfenninger, Stefan; Gauché, Paul; Damerau, Kerstin; Wagner, Fabian; Patt, Anthony (Energy Policy, 2014)
In a recent article, Trainer argues that electricity from concentrating solar power (CSP) in winter would be unreliable and prohibitively expensive, even if generated in premium desert sites. However, he does not carry out a detailed analysis of the reliability or the cost, but bases his conclusion on five arguments, each of which is either irrelevant or erroneous. In particular, his research question, concerning the cost of a CSP kilowatt-hour during winter is irrelevant, and the answer misleading, because the power station will deliver electricity in summer too. A more relevant and not misleading question would be about the performance - the yearly levelised costs of electricity and the reliability - of a CSP fleet. We argue based on a detailed analysis of the performance of CSP in four deserts worldwide, that a coordinated fleet of CSP stations can indeed provide fully dispatchable electricity, and in some cases even baseload, at low cost.
CRIS-Team Scopus Importer:2023-06-14
Keywords: Concentrating solar power; Dispatchability; Levelised cost of electricity; Reliability